Exploring The Global Slack Hypothesis On Inflation Dynamics: A Study In ASEAN-5 - I Made Suidarma; I Nyoman Arta Yasa; Ni Putu Nina Eka Lestari; I Dewa Ketut Gede Prabawa; Ni Wayan Lasmi; I Nyoman Sunarta (Universitas Pendidikan Ganesha, 2023)
Inflation is one of the economic problems that often occur in ASEAN-5 countries. External factors affecting inflation such as changes in energy prices and commodity prices (agriculture, metals, and minerals) can affect inflation in ASEAN-5 countries through the influence of global slack. Therefore, this study was conducted to examine the effect of global slack on domestic inflation dynamics in ASEAN-5 countries by considering the effect of energy price index and commodity price index (agriculture, metals, and minerals) on domestic inflation. The data analysis method used is the Panel of Vector Error Correction Model (VECM-Panel) by considering the effect of energy price index and commodity price index (agriculture, metals, and minerals) on domestic inflation in ASEAN-5. The results show that there is an influence of global slack on domestic inflation in ASEAN-5 countries, especially through the energy price index and commodity price index. Energy prices affect inflation in both the short and long run, whereas commodity prices only affect long-term inflation. The implication of the results of this study is the importance of the role of global commodity price stability policy in maintaining domestic price stability in ASEAN-5.